QTLs and Potential Candidate Genes for Heat Stress Tolerance Identified from the Mapping Populations Specifically Segregating for Fv/Fm in Wheat - Sharma, Dew Kumari; Torp, Anna Maria; Rosenqvist, Eva; Ottosen, Carl-Otto; Andersen, Sven B. (Frontiers in Plant Science, 2017)
Despite the fact that Fv/Fm (maximum quantum efficiency of photosystem II) is the most widely used parameter for a rapid non-destructive measure of stress detection in plants, there is barely thorough study on genetic understanding of this trait under heat stress. Our aim was to identify quantitative trait locus (QTL) and the potential candidate genes linked to Fv/Fm for improved photosynthesis under heat stress in wheat (Triticum aestivum L.). Three bi-parental F2 mapping populations were generated by crossing three heat tolerant male parents (origin: Afghanistan and Pakistan) selected for high Fv/Fm with a common heat susceptible female parent (origin: Germany) selected for lowest Fv/Fm out of a pool of 1274 wheat cultivars of diverse geographic origin. Parents together with 140 F2 individuals in each population were phenotyped by Fv/Fm under heat stress (40°C for three days) around anthesis. The Fv/Fm decreased by 6.3% in the susceptible parent, 1-2.5% in the tolerant parents and intermediately 4-6% in the mapping populations indicating a clear segregation for the trait. The three populations were genotyped with 34,955 DArTseq and 27 SSR markers, out of which ca. 1800 polymorphic markers mapped to 27 linkage groups covering all the 21 chromosomes with a total genome length of about 5000 cM. Inclusive composite interval mapping resulted in the identification of one significant and heat-stress driven QTL in each population on Day 3 of the heat treatment, two of which were located on chromosome 3B and one on chromosome 1D. These QTLs explained about 13-35% of the phenotypic variation for Fv/Fm with an additive effect of 0.002 to 0.003 with the positive allele for Fv/Fm originating from the heat tolerant parents. Approximate physical localization of these three QTLs revealed the presence of 12 potential candidate genes having a direct role in photosynthesis and/or heat tolerance. Besides providing an insight into the genetic control of Fv/Fm in the present study, the identified QTLs would be useful in breeding for heat tolerance in wheat.